PENGARUH METODE QUANTUM TEACHING TERHADAP HASIL BELAJAR PADA MATERI SPU KELAS X SMA - Nur Azizah; Rachmat Sahputra; Rody Putra Sartika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe aim of this research is to determine the influence of the quantum teaching methods on student learning outcomes on the Periodic System of elements material at SMA Negeri 2 Mempawah Hilir. The form of research is used a quasi experimental design with a nonequivalent control group design. The sample of this research was class X MIPA 1 as a control class totaling 26 students and class X MIPA 2 as an experimental class totaling 24 students, with a population of class X MIPA totaling 50 students, and using saturated sampling techniques. Data collection techniques that is giving a score of answers to the questions pretest and posttest with data collection tools in the form of learning outcomes tests and interviews as supporting data. The indicator in this research is to explain how to charge electrons according to the Hund rules and Aufbau principles and to group the groups and periods of an element in the periodic table. Based on the analysis using the Mann Whitney U test (α = 5%) that is 0.001 ≤ 0.05 shows that there are differences in learning outcomes between students who are taught using the quantum teaching methods and students who are taught using conventional methods. The value of the effect size obtained was 1.64 and gave an effect of 44.95% to the increase in student learning outcomes.Keywords: Learning Outcomes, Periodic System of Elements, Quantum Teaching